2020
DOI: 10.17221/292/2019-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of co-encapsulation of Bifidobacterium animalis subsp. lactis Bb12 with inulin and ascorbic acid on its viability

Abstract: Eight types of capsules containing Bifidobacterium animalis subsp. lactis Bb12 with addition of inulin and/or ascorbic acid were prepared by emulsion method with milk protein matrix or by extrusion method with alginate matrix. The size of protein and alginate capsules containing only Bb12 was 204 ± 18 µm and 1.7 ± 0.1 mm, respectively. Addition of both inulin (1% w/w) and ascorbic acid (0.5% w/w) increased the size of alginate capsules. Both methods of encapsulation prevented efficiently the manifestation of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Obviously, the EE and SR of probiotics encapsulated in the microcapsules containing FOS and the fish oil complex were higher than that without additional substrates ( p < 0.05) and the highest values of 95.9% and 95.5% for the EE and SR were obtained at the eighth sample, which included 2% FOS and 20 µL fish oil. It had also been reported that the alginate capsules containing the complex of inulin (1%, w / w ) and ascorbic acid (0.5%, w / w ) greatly enhanced the viability of Bifidobacteria in simulated gastrointestinal fluids [ 24 ]. Therefore, a combination of 2% FOS and 20 µL fish oil was identified as the best formulation to prepare the SPI-O-F-L-P microcapsules.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the EE and SR of probiotics encapsulated in the microcapsules containing FOS and the fish oil complex were higher than that without additional substrates ( p < 0.05) and the highest values of 95.9% and 95.5% for the EE and SR were obtained at the eighth sample, which included 2% FOS and 20 µL fish oil. It had also been reported that the alginate capsules containing the complex of inulin (1%, w / w ) and ascorbic acid (0.5%, w / w ) greatly enhanced the viability of Bifidobacteria in simulated gastrointestinal fluids [ 24 ]. Therefore, a combination of 2% FOS and 20 µL fish oil was identified as the best formulation to prepare the SPI-O-F-L-P microcapsules.…”
Section: Resultsmentioning
confidence: 99%
“…Emulsification is an effective technique to protect biocompounds and probiotics from gastrointestinal conditions, as shown by Kumherová et al 129 In their study, they proved that emulsification provides the same protective effect for probio-…”
Section: Emulsificationmentioning
confidence: 87%
“…Emulsification is an effective technique to protect biocompounds and probiotics from gastrointestinal conditions, as shown by Kumherová et al 129 In their study, they proved that emulsification provides the same protective effect for probiotics as ionic gelation. In this case, the emulsification was carried out in a water-in-oil emulsion of the fresh culture of probiotic Bifidobacterium animalis subsp.…”
Section: Encapsulation Techniques: An Efficient Strategy To Deliver B...mentioning
confidence: 89%
“…The extrusion technique is carried out by first mixing probiotic cells with wall material solution (Silva et al, 2018). Besides that, other ingredients such as prebiotics or active ingredients are also added to the mixture of probiotic and wall materials solution prior to the extrusion (Kumherová et al, 2020). The mixture will then be extruded through either syringe needle or monocentric nozzles to produce droplets and dropped into a hardening solution (Kailasapathy, 2002; Serna‐Cock & Vallejo‐Castillo, 2013) (Figure 2).…”
Section: Microencapsulationmentioning
confidence: 99%